OCTOPUS (Octopus cyanea) CATCHING AREA USING HANDLING IN THE BARRANG CADDI ISLAND AREA USING REMOTE SENSING METHOD - Hairullah Hairullah; Fathuddin Fathuddin; Muh. Ikhsan Idrus; Arnold Kabangnga (Jurnal Riset Diwa Bahari (JRDB), 2026)
This study aimed to identify potential fishing grounds for the blue octopus (Octopus cyanea) around Barrang Caddi Island, Makassar City, by integrating field observations with remote sensing-based oceanographic parameters. A quantitative descriptive survey was employed by accompanying local fishermen during 21 fishing trips using handline (handline hook) gear. Geographic coordinates of fishing locations were recorded using a Global Positioning System (GPS), while satellite-derived sea surface temperature (SST), salinity, and chlorophyll-a concentration were obtained from Aqua MODIS and HYCOM datasets. Spatial analysis was performed using Geographic Information Systems (GIS) to delineate potential fishing zones based on the integration of catch distribution and environmental variables. The results revealed that potential fishing grounds were predominantly located in shallow coral reef habitats surrounding Barrang Lompo and Barrang Caddi Islands. Sea surface temperature averaged 29.24°C, salinity reached 30.8 PSU, and chlorophyll-a concentration ranged from 0.6 to 0.8 mg m⁻³, indicating environmentally favorable conditions for Octopus cyanea. Moderate-potential fishing zones occupied the largest spatial extent, whereas high-potential areas were concentrated near structurally complex coral reef ecosystems. These findings demonstrate that remote sensing provides an effective approach for identifying productive octopus fishing grounds and can support sustainable fisheries management, improve fishing efficiency, and provide scientific information for spatial planning and resource conservation in the Spermonde Archipelago.